Assessment of metal bioavailability in the vineyard soil-grapevine system using different extraction methods. (1st October 2016) - Vázquez Vázquez, Francisco A.; Pérez Cid, Benita; Río Segade, Susana
Highlights: Metal availability in the soil-grapevine system was assessed using extraction methods. Single-step extraction showed similar predictive ability to the sequential extraction. Most of elements studied were weakly mobilized in the vineyard soils. Total metal content showed different accumulation pattern in leaves and grapes. The bioavailable content from soils was related with the found in leaves and grapes. Abstract: This study was focused on the assessment of single and sequential extraction methods to predict the bioavailability of metals in the vineyard soil-grapevine system. The modified BCR sequential extraction method and two single-step extraction methods based on the use of EDTA and acetic acid were applied to differently amended vineyard soils. The variety effect was studied on the uptake of metals by leaves and grapes. Most of the elements studied (Ca, Mg, Cu, Fe, Mn, Zn and Pb) were weakly mobilized from vineyard soils, with the exception of Cu and Mn. The determination of total metal content in leaves and grapes showed a different accumulation pattern in the two parts of the vine. A significant relationship was observed, for all the elements studied except for Fe, between the content bioavailable in the soil and the accumulated in both leaves and grapes (R = 0.602–0.775, p < 0.01).